The IDB: An ice core geodatabase for paleoclimatic and glaciological analyses - MATTAVELLI, MATTEO; STRIGARO, DANIELE; FRIGERIO, IVAN; DE AMICIS, MATTIA GIOVANNI MARIA; Locci, F; Melis, M (Comitato Glaciologico Italiano, 2016)
The Italian national project, NEXTDATA, is focused to favour the implementation of measurements networks in remote mountain and marine areas and develop efficient database structure to archive and access meteoclimatic and paleoclimatic proxies derived from ice core, marine core, tree ring and pollen. They give precious information about the evolution of anthropogenic pollution, climate variability and about the composition of middle troposphere. The main object of this work is to develop the Ice core DataBase (IDB), an interoperability architecture based on a spatial database that contains physical and chemical characterization data about non-polar ice core. The principal scope is to build an efficient web portal where paleo-scientist can easily and quickly access to specific proxy data useful for paleoclimatic analysis. The ice core geographic information is useful to evaluate the glacier suitability for ice core drilling of mountain glaciers and to reconstruct the last 2k of Italy climatic history. Starting with an accurate bibliography research we managed to collect a great amount of ice core data and metadata that were essential to study a suitable methodology to reach the study goals. Data collected were integrated in an information system through specific web services. The developed applications were based on open source software tools such as PostgreSQL and PostGIS for database, Geoserver and Leaflet for webGIS. The geospatial services were implemented with the technical specifications proposed by OGC and INSPIRE standards in order to maximize data interoperability.